REPRODUKSI PEREMPUAN DALAM PERSPEKTIF ISLAM (Tinjauan terhadap Haid, Nifas, dan Istihadhah) - Nurdeni Dahri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
The article explains about haidh, nifas and istihadhah according to Islamic view. Islam has a positive view on a woman who is undrgoing menstruation, nifas and istihadhah, because Islam very cares with woman reproduction health. None of the texts that consider woman who is undergoing the process of reproduction is as a dirty person and should be shunned. Likewise fiqh substantially negative view of women's reproductive process, although in some specific law product, fiqh does not reflect gender sensitivity. Real conditions of women should be the primary reference in all laws and regulations concerning menstrual problems, nifas and istihadhah. Reproductive rights of women are supposed to be guaranteed in any legal formulation. For ensure the reproductive rights of women equal to sustain human life and its descendants (hifdz annasl) which is one of the goals of Islamic Shariah (maqasid ash-shari'ah).